PsycEXTRA Dataset 2013
DOI: 10.1037/e505772014-202
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mindfulness Meditation on Time Perception

Abstract: Research has increasingly focussed on the benefits of meditation in everyday life and performance. Mindfulness in particular improves attention, working memory capacity, and reading comprehension. Given its emphasis on moment-to-moment awareness, we hypothesised that mindfulness meditation would alter time perception. Using a within-subjects design, participants carried out a temporal bisection task, where several probe durations are compared to "short" and "long" standards. Following this, participants either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…We used FFMQ that measured trait mindfulness, and hence it is plausible that trait mindfulness was improved in the present study. However, several previous studies have revealed that short exercises promoted state mindfulness (Kramer et al, 2013;Schofield et al, 2015;Arch & Craske, 2006). It is possible that exposure to negative events and meditation exercise modulate state mindfulness, and this modulation is, in turn, involved with in our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used FFMQ that measured trait mindfulness, and hence it is plausible that trait mindfulness was improved in the present study. However, several previous studies have revealed that short exercises promoted state mindfulness (Kramer et al, 2013;Schofield et al, 2015;Arch & Craske, 2006). It is possible that exposure to negative events and meditation exercise modulate state mindfulness, and this modulation is, in turn, involved with in our results.…”
Section: Discussionmentioning
confidence: 99%
“…The experimenter sat with the participants to ensure task compliance. This exercise was designed for individuals with no prior experience of mindfulness meditation and has been used in extensively in previous studies (Kramer et al, 2013;Erisman & Roemer, 2010;Mirams et al, 2013;Segal, Williams, & Teasdale, 2002). After engaging in mindfulness meditation, the participants again responded to the Japanese version of the FFMQ in the post-questionnaire block.…”
Section: B Stimuli and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with that, longer subjective time units were shown in Mindfulness Meditation practitioners compared to control participants (Berkovich‐Ohana et al, ). In later studies, control participants as well as experienced meditators showed a relative time expansion for stimuli in the millisecond‐to‐second range directly after a mindfulness meditation session (Droit‐Volet et al, ; Kramer, Weger, & Sharma, ). Recent cross‐sectional studies comparing experienced meditators with meditation‐naive controls in the ability to judge duration showed how subjective time in everyday experience is slowed in mindfulness meditators (Wittmann et al, ) while the accuracy in time perception is increased in Transcendental Meditation practitioners (Schötz et al, ).…”
Section: Meditation Meditators and Time Perceptionmentioning
confidence: 98%
“…When a conscious state varies, psychological time is experienced differently. For example, time dilation is experienced when an organism is aroused (e.g., threat, van Wassenhove et al 2008), or experiences heightened consciousness (e.g., during meditation, Kramer et al 2013). Temporal duration also fluctuates in altered states of consciousness (e.g., near-death experiences, Wittmann & Paulus 2008).…”
Section: Microgenymentioning
confidence: 99%